2016
DOI: 10.1186/s12889-016-3477-z
|View full text |Cite
|
Sign up to set email alerts
|

The risk of late or advanced presentation of HIV infected patients is still high, associated factors evolve but impact on overall mortality is vanishing over calendar years: results from the Italian MASTER Cohort

Abstract: BackgroundWe aimed at evaluating frequency and factors associated with late presentation and advanced HIV disease and excess risk of death due to these conditions from 1985 to 2013 among naïve HIV infected patients enrolled in the Italian MASTER Cohort.MethodsAll antiretroviral naive adults with available CD4+ T cell count after diagnosis of HIV infection were included. Multivariable logistic regression analysis investigated factors associated either with late presentation or advanced HIV disease. Probabilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
29
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
8
29
2
1
Order By: Relevance
“…Compared to the early presenters, great majority of late presenters had died in the current study, and this is similar with findings from other studies conducted elsewhere [ 54 , 55 ]. It is plausible therefore to argue that late presentation leads to a greater risk of: rapid progression to advanced AIDS stage, compromised immune response, poor treatment response, and finally death [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Compared to the early presenters, great majority of late presenters had died in the current study, and this is similar with findings from other studies conducted elsewhere [ 54 , 55 ]. It is plausible therefore to argue that late presentation leads to a greater risk of: rapid progression to advanced AIDS stage, compromised immune response, poor treatment response, and finally death [ 3 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar trends of declining late presentation were reported within Collaboration of Observational HIV Epidemiological Research Europe (COHERE) study for the period of 2001–2010, which then stabilized during 2010–2013 at 48–49% [ 2 , 18 ]. Similar to COHERE study, recent reports from western European countries indicate the prevalence of late presentation of around 50% [ 19 21 ]. The data for Eastern European (EE) region is scarce.…”
Section: Discussionsupporting
confidence: 78%
“… 16 Similar findings were observed in Italian study, conducted in 2016, where IDU and older age were positively associated with late presentation. 17 In contrast to our findings, comparison of two groups of late and early testers in the United States found that late testers were significantly more likely to be having been exposed to HIV through heterosexual contacts, although the researches defined the late testers as persons who had their first positive HIV test <1 year before the diagnosis of AIDS. 18 Girardi et al showed that in Italy, IDU significantly increased the probability of delayed presentation to medical care after being tested HIV-positive but reduced the chance of late testing (CD4 count <200 cell/mm 3 ).…”
Section: Discussioncontrasting
confidence: 99%